A Strobilanthes (Acanthaceae) miscellany - Wood, JRI; Scotland, RW (Springer, 2021)
This paper presents miscellaneous, previously unpublished results arising from the authors’ research into Strobilanthes. S. moylaniae J.R.I.Wood & Scotland from New Guinea and S. dengii J.R.I.Wood & Scotland from Sumatra are proposed as new species, while an unnamed species is described from Sumba Island in Indonesia in the hope that it might be rediscovered. A new subspecies, subsp. subovata J.R.I.Wood & Scotland is described for S. timorensis Nees, while attention is drawn to its plietesial flowering pattern. The new combinations S. benculensis (Bremek.) J.R.I.Wood & Scotland, S. wetarensis (Bremek.) J.R.I.Wood & Scotland, S. javanica (Bremek.) J.R.I.Wood & Scotland and S. serpens (Nees) J.R.I. Wood & Scotland are made. Typification is clarified and where appropriate lectotypes are designated for Hemigraphis hispidula Craib, Lepidagathis setigera Blume, Ruellia crispa L., R. sabiniana Lindl., Strobilanthes duclouxii Benoist, S. erecta C.B.Clarke, S. flava Kurz, S. forrestii Diels, S. scabra Nees, S. secunda T.Anderson and S. thomsonii T.Anderson.